Mycorrhizal Communities and Isotope Signatures in Two Partially Mycoheterotrophic Orchids - Jacquemyn, Hans; Brys, Rein; Waud, Michael; Evans, Alexandra; Figura, Tomáš; Selosse, Marc-André (Frontiers in Plant Science, 2021)
Partial mycoheterotrophy, the ability of plants to obtain carbon from fungi throughout their life cycle in combination with photosynthesis, appears to be more common within the Plant Kingdom than previously anticipated. Recent studies using stable isotope analyses have indicated that isotope signatures in partially mycoheterotrophic plants vary widely among species, but the relative contributions of family- or species-specific characteristics and the identity of the fungal symbionts to the observed differences remain unclear. Here, we investigated in detail mycorrhizal communities and isotopic signatures in four co-occurring terrestrial orchids (Platanthera chlorantha, Epipactis helleborine, E. neglecta and the mycoheterotrophic Neottia nidus-avis). All investigated species were mycorrhizal generalists (i.e., associated with a large number of fungi simultaneously), but mycorrhizal communities differed significantly between species. Mycorrhizal communities associating with the two Epipactis species consisted of a wide range of fungi belonging to different families, whereas P. chlorantha and N. nidus-avis associated mainly with Ceratobasidiaceae and Sebacinaceae species, respectively. Isotopic signatures differed significantly between both Epipactis species, with E. helleborine showing near autotrophic behavior and E. neglecta showing significant enrichment in both carbon and nitrogen. No significant differences in photosynthesis and stomatal conductance were observed between the two partially mycoheterotrophic orchids, despite significant differences in isotopic signatures. Our results demonstrate that partially mycoheterotrophic orchids of the genus Epipactis formed mycorrhizas with a wide diversity of fungi from different fungal families, but variation in mycorrhizal community composition was not related to isotope signatures and thus transfer of C and N to the plant. We conclude that the observed differences in isotope signatures between E. helleborine and E. neglecta cannot solely be explained by differences in mycorrhizal communities, but most likely reflect a combination of inherent physiological differences and differences in mycorrhizal communities.